Design and synthesis of dopant-free organic hole-transport materials for perovskite solar cells. Issue 69 (25th July 2018) - Wang, Linqin; Zhang, Jinbao; Liu, Peng; Xu, Bo; Zhang, Biaobiao; Chen, Hong; Inge, A. Ken; Li, Yuanyuan; Wang, Haoxin; Cheng, Yi-Bing; Kloo, Lars; Sun, Licheng
Abstract : Two novel dopant-free hole-transport materials for perovskite solar cells with spiro[dibenzo[ c, h ]xanthene-7, 9′-fluorene] skeletons were prepared via facile synthesis routes. Abstract : Two novel dopant-free hole-transport materials (HTMs) with spiro[dibenzo[ c, h ]xanthene-7, 9′-fluorene] (SDBXF) skeletons were prepared via facile synthesis routes. A power conversion efficiency of 15.9% in perovskite solar cells is attained by using one HTM without dopants, which is much higher than undoped Spiro-OMeTAD-based devices (10.8%). The crystal structures of both new HTMs were systematically investigated to reveal the reasons behind such differences in performance and to indicate the design principles of more advanced HTMs.